Bi-layered constructs based on poly(L-lactic acid) and starch for tissue engineering of osteochondral defects - Ghosh, Satyabrata (2008)
Articular cartilage has a limited capacity to repair itself, and conventional therapeutic approaches have shown to have limited success as they are deficient and inconsistent in long-term repair. Tissue engineering has shown to be an alternative route to regenerate articular defects. In this work, new bi-layered scaffolds are developed in order to enhance the integration between the engineered cartilage tissue and the corresponding subchondral bone. The concept includes the use of a common polymer in both sides, poly(L-lactic acid), PLLA, to increase the bonding between them, and the use of compression moulding followed by particle leaching to process porous scaffolds with controllable porosities. A compact layer could be observed between the two layers that could be useful for independent cell culturing of the developed osteochondral constructs. A blend of starch and PLLA was used in the cartilage side, which was found to possess adequate hydration capability. For the bone region, where more stiffness and strength was required, PLLA reinforced with hydroxyapatite was used. Preliminary bioactivity tests demonstrated that the bone-layer could induce the formation of a calcium–phosphate layer in vitro, whereas the cartilage layer does not exhibit the ability for calcification.